Navigation of a virtual exercise environment with Microsoft Kinect by people post-stroke or with cerebral palsy. Issue 4 (1st October 2016) - Pool, Sean M.; Hoyle, John M.; Malone, Laurie A.; Cooper, Lloyd; Bickel, C. Scott; McGwin, Gerald; Rimmer, James H.; Eberhardt, Alan W.
ABSTRACT: One approach to encourage and facilitate exercise is through interaction with virtual environments. The present study assessed the utility of Microsoft Kinect as an interface for choosing between multiple routes within a virtual environment through body gestures and voice commands. The approach was successfully tested on 12 individuals post-stroke and 15 individuals with cerebral palsy (CP). Participants rated their perception of difficulty in completing each gesture using a 5-point Likert scale questionnaire. The "most viable" gestures were defined as those with average success rates of 90% or higher and perception of difficulty ranging between easy and very easy. For those with CP, hand raises, hand extensions, and head nod gestures were found most viable. For those post-stroke, the most viable gestures were torso twists, head nods, as well as hand raises and hand extensions using the less impaired hand. Voice commands containing two syllables were viable (>85% successful) for those post-stroke; however, participants with CP were unable to complete any voice commands with a high success rate. This study demonstrated that Kinect may be useful for persons with mobility impairments to interface with virtual exercise environments, but the effectiveness of the various gestures depends upon the disability of the user.